TASK SCHEDULING OPTIMISATION OF DISTRIBUTED REAL-TIME COMPUTING SYSTEMS. - Stanko, Petro; Ohremchuk, Olena; Salamatina , Daria; Sverdlova, Daria (Science-based technologies, 2024)
Distributed computing structures for production and special purposes represent the resources of soft or hard real-time systems. The problem of task planning is to determine the optimal distribution according to the generalized criterion of system utility. The article discusses the methods of building a schedule, based on the theory of planning. It is shown that the most effective step in this process is the optimisation of the activity of the enterprises or organizations at all levels - economic, technical, informational, etc., under the conditions of natural limitations on time resources. Since the optimisation of schedule planning occupies a fundamentally important place in the process of organizing the effective operation of a distributed multiprocessor computing system, the possibilities of using this theory in creating an optimal schedule based on the theory of queues with ordinary and marked applications are considered. The theoretical basis of the planning optimisation problem is a multistage system with M storage units and a set of N´M services. In order to organize the schedule optimality criteria to ensure ease of description, storage and software implementation, a conditional division of criteria into geographic, technical or transit categories with a description of the corresponding priority value is proposed. Taking into account these components, an expression for the average waiting time in the queue for a marked demand is derived. The scheme of the conceptual approach to the construction of a multi-core computer with the distribution of periodic and sporadic tasks is presented. The scheme of the real-time system (RTS) in hardware and software implementation is also presented. Background streams in RTS are activated by RT operating system (RT OS) commands and are embedded in primary streams. The above demonstrates the versatility of the proposed approach to scheduling a multiprocessor computing structure and its ability to meet the user's work requirements in real time.